An evaluation of anatomy teaching in a clinically integrated veterinary curriculum - Gummery, Erica (2019)
Anatomy is a traditional subject, and remains largely unchanged despite developments in higher education and advances in veterinary practice. The research for this thesis aimed to investigate the impact of practical anatomy teaching in a modern, clinically integrated veterinary curriculum.